2018
DOI: 10.1080/21501203.2018.1518934
|View full text |Cite
|
Sign up to set email alerts
|

Fungal diversity of mangrove-associated sponges from New Washington, Aklan, Philippines

Abstract: Sponge-associated fungi are the least explored marine fungal groups. It is only in recent years that fungal symbionts of marine sponges have received attention mainly due to the isolation of bioactive metabolites while not much attention was given to their specificity, biogeography and exact roles in marine sponges. The diversity of fungi associated with mangrove sponges ( Axinella sp., Halichondria cf. panicea, Haliclona sp., Ted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 66 publications
1
20
0
3
Order By: Relevance
“…Gradually, with the exception of those growing on CMA, the colonies developed aerial mycelium and appeared as green, brown, and black filamentous fungi. This type of incubation period dependent morphological dimorphism is not reported in studies describing fungi from marine sponges [39, 47] or other sources [30]. This form of transformation is not the same as temperature-dependent fungal dimorphism which is commonly observed in some fungal species [49].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Gradually, with the exception of those growing on CMA, the colonies developed aerial mycelium and appeared as green, brown, and black filamentous fungi. This type of incubation period dependent morphological dimorphism is not reported in studies describing fungi from marine sponges [39, 47] or other sources [30]. This form of transformation is not the same as temperature-dependent fungal dimorphism which is commonly observed in some fungal species [49].…”
Section: Resultsmentioning
confidence: 83%
“…The existence of yeast-like fungi was identified primarily by microscopic observation of the yeast form using wet mount and lacto phenol cotton blue stain preparations [36]. Further morphological identification was attained by growth on standard fungal media of malt extract agar (MEA) [37], cornmeal agar (CMA) [38], potato dextrose agar (PDA) [30, 39], and Sabouraud dextrose agar (SDA) [40]. All identification media were supplied by Oxoid.…”
Section: Methodsmentioning
confidence: 99%
“…4, all isolates are the member of ascomycetes that are grouped into three clades based on the phylogenetic distance. Calabon et al (2018) reported that ascomycetes are also the dominant fungal group in the mangrove-associated sponge in New Washington, Philippines. They also reported that Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Trianto et al (2017) stated that anthropogenic activity gave influence to the biological activity of the spongeassociated fungi. The latest study on sponge-associated fungi from mangrove ecosystem was performed by Calabon et al (2018). They mentioned that from 22 genera of ascomycetes from mangrove-originated sponge in Aklan, Philippines, Aspergillus was the most dominant genus with 23 isolates followed by Mycelia (n = 21 isolates) and Penicillium (n = 14 isolates).…”
Section: Introductionmentioning
confidence: 99%
“…Ekosistem mangrove memiliki vegetasi yang memberikan manfaat dan fungsi yakni mengurangi resiko abrasi (Hilmi et al, 2014), kemampuan untuk meredam gelombang pasang dan resiko tsunami (Massel et al, 1999;Hilmi et al, 2019;Kerr et al, 2006;Chang et al, 2019), habitat berbagai mikroorganisme (Elison, 2008;Calabon et al, 2019), sebagai sumber pangan (Baderan et al, 2014).…”
Section: Pendahuluanunclassified